The mechanism of dynamic knee valgus and the concurrent validity and reliability during single leg squat in physically active females - Jamaludin, Nazatul Izzati (2022)
Excessive dynamic knee valgus (DKV) or inward movement of the knee during motions is due to the altered kinematics of hip (i.e., top-down kinetic chain) and ankle (i.e., bottom-up kinetic chain) joints. Excessive DKV during motions is a major predictor of lower limb injuries, particularly in females, and can be measured using single leg squat (SLS) tests. However, its mechanism and kinetic chain during SLS are unknown. Therefore, the primary goal of the current study was to elucidate the mechanism of DKV, which include top-down (i.e., influence of hip musculature on motions at knee joint) and bottom-up kinetic chain (i.e., influence of ankle musculature on motions at knee joint), among physically active females. The secondary goal is to examine the validity of 2-Dimensional (2-D) and 3-Dimensional (3-D) motion capture methods in evaluating knee angle during SLS at two squat depths and the within-and between-days reliability of these methods. 34 participants went through screening test and divided into two groups (i.e., normal DKV and excessive DKV group). Then, 3-D knee kinematics (i.e., joint angle) during SLS test at 45° and 60° of knee flexion were observed. The same SLS test was repeated to examine within-and between-days reliability. The motions were captured simultaneously by digital cameras in frontal and sagittal planes with 3-D infrared cameras to examine the validity between the both methods in evaluating knee angle. Weight-Bearing Lunges Test was conducted to evaluate their ankle range of motion (ROM). Ankle and Hip Isokinetic Strength was tested at 180°/s angular velocity in ankle dorsiflexion, plantarflexion, inversion and eversion and hip flexion, extension, abduction and adduction for both legs. Pearson correlation was used to examine the relationships between hip, ankle strength and ankle ROM and knee kinematics during SLS at both angles. Intraclass Correlation Coefficient (ICC) was used as indicator for within-and between-days reliability test of both groups. Bland-Altman Plot and Pearson correlation were used to illustrate the validity of 2-D and 3-D motion capture methods. Normal DKV group shows significant relationships between dominant hip adduction strength (r=-0.51, p=0.04), non-dominant hip extension strength (r=-0.56, p=0.02) and knee angle during SLS. Significant relationship was noticed between non-dominant hip abduction strength and knee angle during SLS (r=-0.53, p=0.03) in excessive DKV group. Next, there were significant relationships between dominant ankle angle (r=0.51, p=0.04) and distance (r=-0.53, p=0.03) with knee angle in normal group, and between non-dominant ankle angle during 45° knee flexion (r=0.51, p=0.04) and non-dominant ankle angle during 60° knee flexion (r=0.50, p=0.04) with knee angle in excessive DKV group. Next, both methods of evaluating knee angle at both squat depths are shown valid for both legs in normal group. However, the methods are valid only for non-dominant leg during SLS at 60° knee flexion for excessive DKV group. Thus, both groups demonstrated the influence of the top-down and bottom-up kinetic chains on knee kinematics during SLS, with distinct muscle groups being emphasised in each group. Besides, SLS is a valid and reliable test for 2-D and 3-D methods of studying knee angles at squat depths of 45° and 60° knee flexion for participants with normal and excessive DKV groups.